Influence of virtual reward systems on perceptions of enjoyability, output quality and effort - Liu, Yao (2017)
Human computation has been successfully applied to deal with complex issues in our daily life and it has been widely used in the crowdsourcing field. A human computation game refers to the harnessing of human wisdom to address computational problems through enjoyable gameplay and to collect information by motivating players to contribute their efforts to the addressing of problems with the enjoyment as a return. Human computation games are characterized by obvious gamification features, and the virtual reward system is an essential element. Different kinds of virtual reward systems have different influences on users’ perceptions from multiple aspects, including the perceived enjoyability, perceived output quality and perceived effort. This article explores factors that are likely to have an impact on the users’ perception of enjoyability, output quality as well as the effort that results from virtual reward systems. Three mobile apps for crowdsourcing location-based content are developed: which are SHARE, a control app without any reward features; POINT, an experimental app with point reward system and BADGE, an experimental app with badge reward system. The research randomly assigned 150 participants to use an app on Android-based mobile phone and upon task completion, they were required to fill up questionnaires, which elicit their perceived enjoyability, perceived output quality, perceived effort, as well as an overall evaluation. With regard to perceived enjoyability, results suggest that it can be driven by virtual reward systems from the underlying factors, including focused attention, involvement, novelty, endurability, aesthetics and perceived usability. When it comes to perceived output quality, findings indicate that it can be affected by virtual reward systems from the exanimated five variables, namely accuracy, completeness, relevance, timeliness and overall information quality. As to perceived effort, results show that the types of virtual reward systems have impacts on perception of developer’s effort, self-effort and other participants’ effort.